A Quality Improvement Initiative to Improve Discharge Timeliness and Documentation. Issue 4 (July 2021) - Larrow, Annie; Chong, Amy; Robison, Treavor; Patel, Aarti; Kuelbs, Cynthia; Fisher, Erin; Hershey, Daniel; Pierce, Heather
Abstract : Introduction: Discharge communication is critical for the continuity of patient care. However, discharge summaries are often not available in time for follow-up visits, and the content is inconsistent. We aimed to decrease the average time to discharge summary completion by 25%, reduce deficiencies (information errors) by 50%, and increase discharge summary template use to >80% in 6 months. Methods: A pediatric interprofessional team used quality improvement methods to identify barriers and implement interventions, including discharge summary completion time expectation, electronic health record discharge summary template changes addressing gaps, and training. Notable changes to the template included embedded writing tips to guide writers and specific template choices for common diagnoses to standardize content. The primary outcome measure was the mean discharge summary completion time. Secondary measures were the percentage of discharge summaries with deficiencies and the rate of template use. Results: After interventions, the mean discharge summary completion time decreased by 70% (from 71.5 to 21.8 hours). Discharge summary deficiencies decreased 44% (from 4.5% to 2.5%), and template use increased from 62% to 97%. Conclusion: Quality improvement methods and a newly designed electronic health record-discharge summary template were used to dramatically improve discharge summary timeliness and standardize content to streamline continuity of care.